ILC2s and fungal allergy - Kita, Hirohito (Allergol Int, 2015)
Innate lymphoid cells (ILCs) have emerged recently as an important component of the immune system and the cell type that regulates mucosal immune responses and tissue homeostasis. Group 2 ILCs (ILC2s), a subset of ILCs, reside in various tissues and are characterized by their capacity to produce type 2 cytokines and tissue growth factors. These ILC2s play an important role in allergic immune responses by linking signals in the atmospheric environment to the immune system. Fungi are one of the major allergens associated with human asthma, and animal and in vitro models using the fungal allergens have provided significant information toward our understanding of the mechanisms of allergic disease. In mouse models of fungus-induced allergic airway inflammation, IL-33, IL-25, and TSLP are released by airway epithelial cells. Lung ILC2s that respond to these cytokines quickly produce a large quantity of type 2 cytokines, resulting in airway eosinophilia, mucus production, and airway hyperreactivity even in the absence of adaptive immune cells. Evidence also suggests that ILC2s interact with conventional immune cells, such as CD4(+) T cells, and facilitate development of adaptive immune response and persistent airway inflammation. ILC2s are also present in respiratory mucosa in humans. Further investigations into the biology of ILC2s and their roles in the pathophysiology of allergic diseases will provide major conceptual advances in the field and may provide useful information toward development of new therapeutic strategies for patients.